P2Y6 receptor-mediated signaling amplifies TLR-induced pro-inflammatory responses in microglia - Timmerman, Raissa; Zuiderwijk-Sick, Ella A.; Bajramovic, Jeffrey J. (Frontiers in Immunology, 2022)
TLR-induced signaling initiates inflammatory responses in cells of the innate immune system. These responses are amongst others characterized by the secretion of high levels of pro-inflammatory cytokines, which are tightly regulated and adapted to the microenvironment. Purinergic receptors are powerful modulators of TLR-induced responses, and we here characterized the effects of P2Y6 receptor (P2RY6)-mediated signaling on TLR responses of rhesus macaque primary bone marrow-derived macrophages (BMDM) and microglia, using the selective P2RY6 antagonist MRS2578. We demonstrate that P2RY6-mediated signaling enhances the levels of TLR-induced pro-inflammatory cytokines in microglia in particular. TLR1, 2, 4, 5 and 8-induced responses were all enhanced in microglia, whereas such effects were much less pronounced in BMDM from the same donors. Transcriptome analysis revealed that the overall contribution of P2RY6-mediated signaling to TLR-induced responses in microglia leads to an amplification of pro-inflammatory responses. Detailed target gene analysis predicts that P2RY6-mediated signaling regulates the expression of these genes via modulation of the activity of transcription factors NFAT, IRF and NF-κB. Interestingly, we found that the expression levels of heat shock proteins were strongly induced by inhibition of P2RY6-mediated signaling, both under homeostatic conditions as well as after TLR engagement. Together, our results shed new lights on the specific pro-inflammatory contribution of P2RY6-mediated signaling in neuroinflammation, which might open novel avenues to control brain inflammatory responses.